Reading Comprehension Difficulties on Students’ Perception in Narrative Text - Laia, Dewi Purnamasari; Pasaribu, Arsen Nahum; Manurung, Lastri Wahyuni (Journal of Language Education (JoLE), 2024)
This research aims to identify the reading comprehension difficulties faced by eleventh-grade students and how to solve the students' reading comprehension difficulties. This research uses mixed methods with an explanatory sequential design to collect data, both quantitative and qualitative. They are reading tests to collect quantitative data and interviews to collect qualitative data. Twenty students from SMKN 1 Lolomatua participated in obtaining quantitative and qualitative data. The research results showed that 76,25% of students experienced difficulty in making conclusions. Second, 44.3 % of students had difficulty determining the main idea. Third, 68,3 % of students have difficulty interpreting vocabulary. Fourth, 45 % of students found it difficult to identify references. Fifth, 52 % of students had difficulty detailing information. Then, four are the strategies to solve students' difficulties in reading comprehension. They are students who have to read a lot of English books, master the vocabulary, and find synonyms and antonym words. For pronunciation, students can use smartphone applications.